MAMPU BENTUK HASIL PENGELASAN "BUTT FLASH" UNTUK BAJA KARBON RENDAH - Sutomo - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
The Simplest welding is Butt Flash welding, because without metals filler to connect each other of base metal. But it use highest electric current to be melting the area surface which will be connected. After sheet sleel have been connected, this result of welding will be rolled ond rolled again. Sometimes this connecting sheet steel cut out because.forming strength of welding decrease. Because this reason, research would like to know the forming strength base on accelcration, voltage and velocity parameter. Theresult of this research are 6/24 mm/sec'; 7,86 volt; 16/24 mm/sec, will produce high forming strength.